2015
DOI: 10.1111/jcmm.12747
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane domain is crucial to the subcellular localization and function of Myc target 1

Abstract: Deregulation of c‐MYC occurs in a variety of human cancers. Overexpression of c‐MYC promotes cell growth, proliferation, apoptosis, transformation and genomic instability. MYC target 1 (MYCT1) is a direct target gene of c‐MYC, and its murine homologue MT‐MC1 recapitulated multiple c‐Myc‐related phenotypes. However, the molecular mechanism of MYCT1 remains unclear. Here, we identified the transmembrane (TM) domain of MYCT1, not the nuclear localization sequence, is indispensable to the vesicle‐associated locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…3L). A similar binding pattern between MYCT1 and CKAP4 in HEK293T cells was also reported in a previous study (35). Because ZO1 plays a critical role in EC functions such as barrier formation, tension, and migration (36) and RHOA regulates endothelial tight junction maintenance and barrier formation in close association with ZO1 (37), we investigated whether there is a functional interplay between MYCT1, ZO1, and RHOA through a series of combined KD and overexpression of these genes in MCEC cells.…”
Section: Myct1 Interacts With Zo1 and Regulates Ec Motility Through A...supporting
confidence: 78%
See 1 more Smart Citation
“…3L). A similar binding pattern between MYCT1 and CKAP4 in HEK293T cells was also reported in a previous study (35). Because ZO1 plays a critical role in EC functions such as barrier formation, tension, and migration (36) and RHOA regulates endothelial tight junction maintenance and barrier formation in close association with ZO1 (37), we investigated whether there is a functional interplay between MYCT1, ZO1, and RHOA through a series of combined KD and overexpression of these genes in MCEC cells.…”
Section: Myct1 Interacts With Zo1 and Regulates Ec Motility Through A...supporting
confidence: 78%
“…Mouse MYCT1 protein shares an 85% sequence identity with the human MYCT1 protein (fig. S11A) (30,35). To determine whether MYCT1 function is conserved between human and mouse, we knocked down human MYCT1 in HUVEC (human umbilical vein endothelial cell) (HUVEC hMKD) cells (fig.…”
Section: Endothelial Myct1 Function Is Evolutionarily Conserved Betwe...mentioning
confidence: 99%
“…This implies that CG1847 could be involved in cell cycle-associated transcription and istargeted on both mitosis and sensory physiology [ 7 , 23 , 24 ]. Furthermore, CG5482 is reported to be a Myc target gene and its expression is directly regulated by dMyc ( Drosophila Myc) in larva [ 25 , 26 ]. Furthermore, c-MYC regulates over 15% of genomic genes through binding to the consensus sequence—termed E-boxes in mammal cells.…”
Section: Evolutionary and Function Linkage Between Drosophimentioning
confidence: 99%
“…In addition to the genes of energy metabolism and immune function, cytoskeletal genes have been identified as candidate growth-related genes in fish ( Salem et al, 2012 ). In this study, we found a differential expression of cytoskeletal genes such as myc target protein 1 homolog ( myct1 ), Golgi apparatus protein 1 ( glg1 ), zinc finger protein 574 ( znf574 ), and actin filament–associated protein 1-like 2 ( afap1l2 ) in the two groups with different growth rates ( Mourelatos et al, 1995 ; Berg et al, 2010 ; Tie et al, 2016 ; Wu et al, 2016 ), suggesting that they play important roles in cell growth, proliferation, apoptosis, and transformation. The protein tyrosine phosphatase 4A (PTP4A) family, consisting of PTP4A1/PRL1, PTP4A2/PRL2, and PTP4A3/PRL3, has been implicated in cell proliferation and tumorigenesis ( Kobayashi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 80%
“…Among the aforementioned DEGs ( Figure 6 ), several DEGs have been identified as candidate genes regulating growth in previous transcriptomic and genomic studies, including scd , ube4b , atp1b , myct1 , b2m , and mhcII ( Xu et al, 2013 ; Wu et al, 2016 ; Lu et al, 2019 ; Zhou et al, 2019 ). These reports provide additional support to our findings of these genes being significantly involved in the modulation of differential growth in different domestic animals.…”
Section: Discussionmentioning
confidence: 99%